Energy use, behavioral change, and business organizations: Reviewing recent findings and proposing a future research agenda. (January 2016) - Andrews, Richard N.L.; Johnson, Evan
Abstract: A sizable literature has begun to emerge on individual energy behavior, but research on energy behavior in business organizations has been far more limited, despite businesses' responsibility for a far larger fraction of energy use, global warming and other impacts. This article reviews studies of energy behavior in businesses, and suggests areas for additional social science research. We conducted a systematic review of bibliographies on energy and behavior, papers presented at recent conferences on behavior and energy, and reference lists of publications thus identified, and keyword searches on energy behavior and business and related topics. From these sources we identified research articles addressing energy behavior in businesses, and categorized them by qualitative content analysis into three levels of analysis: individuals within organizations, organizations, and institutional forces influencing organizations' behavior. Using this method, we found several well-developed research areas but also significant gaps on other important topics. Under-developed topics include factors influencing businesses' adoption of renewable energy; sector-specific studies on barriers to energy innovation; integrated studies of influences on businesses' energy behavior at the individual, organizational and institutional levels; and cross- cultural comparisons. Such studies offer opportunities both for scholarly contributions and for improving business decision-making and public policy.